Alarm Fatigue in Nursing Students Undertaking Clinical Training in Intensive Care Units: A Multicenter Study - Ferrara, Paolo; Carelli, Lara; Ruta, Federico; Delli Poggi, Alessandro; Marasigan, Milannie; Pinna, Barbara; Destrebecq, Anne; Terzoni, Stefano (La Medicina del Lavoro, 2023)
Background: The frequency of alarms from monitors and other electro-medical devices is of great utility but can increase the professional’s workload and expose nurses in the intensive care unit to Alarm Fatigue. A recent study suggested that students in training can also experience the problem during their first clinical experiences in intensive care. Unfortunately, no data are available about the Italian panorama. To explore Alarm Fatigue among Bachelor of Science in Nursing students at the end of their internship experience in intensive care settings. Methods: Multicenter cross-sectional design. A convenience sample of nurses from 3 Italian university hospitals was recruited. The students completed the revised version of the “Alarm Fatigue questionnaire-ita” at the end of the clinical internship in intensive care settings. Results: 130 nursing students were enrolled (response rate 59.36%). The overall level of Alarm Fatigue was Me= 24.5 IQR [17.5, 30.5]. In addition, 9.23% of the sample reported errors or near misses related to Alarm Fatigue during the internship experience. The alarm fatigue level was higher in students who committed “errors/almost errors” (p=0.038) and in “student workers” (p=0.005). Discussion: The extent of alarm fatigue experienced by nursing students requires developing a preventive strategy.